Newly Recorded Panus lecomtei (Fr.) Corner (Basidiomycota: Panaceae) for Indonesia - Putra, Ivan Permana; Hermawan, Rudy; Salman, Ali Bin Abithalib (UI Scholars Hub, 2023)
Panus lecomtei (Polyporales) is reported for the first time from Indonesia at the IPB University Campus Forest (IPBUCF). This species has similar macroscopic features to P. strigellus and P. neostrigosus. This study aimed to confirm the taxonomic position of P. lecomtei found at IPBUCF based on morphological and molecular evidence. The specimens were described by their macroscopic and microscopic characteristics. A phylogenetic approach was used with the internal transcribed spacer 1/2 sequence data. The combination of morphological and molecular analyses confirmed the taxonomic position of our specimens as P. lecomtei. The recorded species was distinguished by gregarious basidiomata, an infundibuliform resembling a funnel, violet during the immature stage to orangish brown in the mature pileus and ellipsoid basidiospore stages. Our specimens were distinguished from P. strigellus by having smaller basidiospores. It was difficult to separate P. lecomtei BO24428 from P. neostrigosus based on morphological characters. However, the BLAST results showed that specimen BO24428 had 99.56% similarity with P. lecomtei. In addition, our phylogenetic tree nested P. lecomtei BO24428 in the P. lecomtei clade. Morphological illustrations and a phylogenetic tree of P. lecomtei are provided. We suggest combining the morphological and molecular evidence in future studies of P. lecomtei from Indonesia